Recognizing Post-Castration Pain in Piglets: A Survey of Swine Industry Stakeholders and the General Public - Neary, Jessica M.; Porter, Nathaniel D.; Viscardi, Abbie V.; Jacobs, Leonie (Frontiers in Animal Science, 2022)
We need validated, practical methods for pain assessment in piglets. Pain assessment can help researchers, veterinarians and industry professionals identify the need for analgesia or other pain management approaches when applying painful procedures, such as surgical castration. A pain assessment tool, the Piglet Grimace Scale (PGS), was previously validated in this context, but it is not widely applied. It is important that the PGS can be applied by a range of people, not just pain assessment experts. Our objective was to study the validity and reliability of PGS ratings applied by swine industry professionals and the general public, to assess its potential utility in non-research applications. To do so, we conducted an online Qualtrics survey in which, after completing a brief online training module and a practice test, 119 respondents were asked to rate 9 piglet images showing facial expressions immediately after surgical castration or sham-handling. Respondents were provided information on the castration treatment for each image and had continuous access to the scale throughout the survey. The survey also contained demographic questions. Industry respondents were recruited through networking, and participants from the general public were recruited through Amazon Mechanical Turk. Four trained experts scored each image, and these scores were averaged to produce gold standard scores. Intraclass correlations indicated strong internal consistency among experts, industry and public. ANOVA demonstrated scoring to be moderately comparable between groups. Campbell and Fiske's Multi-Trait Multi-Method framework provided qualified support for the internal validity and reliability of the PGS scale, even applied by non-experts (industry and public). Both response groups were able to recognize pain in castrated piglets. However, public respondents attributed higher levels of pain to sham-handled piglets than industry respondents (2.83 vs. 2.35; p=0.047), and both response groups systematically overestimated pain experience compared to the experts, suggesting more training may be necessary before using the scale in a diagnostic capacity. Nevertheless, overall findings support wide applicability of PGS, even with minimal training, to improve awareness, recognition and monitoring of swine pain among veterinarians, industry professionals and even members of the public.